2011
DOI: 10.1097/rhu.0b013e31822c53ad
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Adult-Onset Still Disease Successfully Treated With Abatacept

Abstract: Adult-onset Still disease (AOSD) is an inflammatory condition of unknown etiology that responds to glucocorticosteroids and disease-modifying antirheumatic drugs, particularly methotrexate. However, disease refractory to conventional treatment has led to the reported use of biologic therapy including tumor necrosis factor α inhibitors (infliximab, etanercept, and adalimumab), anakinra, rituximab, and tocilizumab. We report the successful use of abatacept in the treatment of a patient with AOSD manifested by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Canakinumab showed some inconsistent results in AOSD [37][38][39] but is currently being investigated for its efficacy on AOSD's joint involvement (NCT02204293). No patient in this study received abatacept or rituximab; the data are very limited but some authors reported efficacy in patients who fail to respond to TNF, IL-1, or IL-6 inhibition [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Canakinumab showed some inconsistent results in AOSD [37][38][39] but is currently being investigated for its efficacy on AOSD's joint involvement (NCT02204293). No patient in this study received abatacept or rituximab; the data are very limited but some authors reported efficacy in patients who fail to respond to TNF, IL-1, or IL-6 inhibition [40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Abatacept (CTLA4IgFc), a fusion protein which consists of the extracellular domain of the cytotoxic T-lymphocyte antigen 4 (CTLA-4) and the Fc portion of immunoglobulin G1 (IgG1), inhibits T-cell activation by binding to CD80 and CD86 receptors on antigen-presenting cells (APCs) and preventing their interaction with CD28 receptor on T cells. Recent findings support a potential role of the latter in AOSD cases refractory to conventional DMARDs, anti-TNF- α agents, and even to IL-1 receptor antagonists [81, 82]. …”
Section: Cytokines As Therapeutic Targets (Table 2)mentioning
confidence: 81%
“…Only two of the 12 patients who switched from other TNF inhibitors, such as infliximab or adalimumab, responded to ETN (3,13,16,18,19,23,24,28,29,31,32), suggesting that physicians should avoid the use of ETN in patients with an inadequate response to other TNF inhibitors. Three patients requiring discontinuation of ETN due to infection have been reported (3,12,30).…”
Section: Discussionmentioning
confidence: 99%